O empreendedorismo na perspectiva de gênero na zona sul do centro comercial de Parnamirim - RN - Fernandes, Weslley Thiago Martins (Universidade Federal Rural do Semi-Árido, 2018)
Today, entrepreneurs are increasingly making the market competitive, making business highly challenging. To compete, it is necessary to have an entrepreneur profile that meets the new changes in the market and becomes the differential in the focus on innovation and collaboration for economic strengthening. With the development of entrepreneurship in the country, and with a view in the scenario in the state of Rio Grande do Norte, observed the possibility of carrying out a study that would characterize the profile of the entrepreneurs and enterprises existing in the commercial south zone of the municipality of Parnamirim- RN. This research was carried out in a direct way, with the use of research techniques and data collection. For the data collection, a questionnaire was applied, with objective and discursive questions in order to evaluate the distribution by gender, the age group of the entrepreneurs, the educational level, the branch of the companies, how the disclosures are made of the businesses, to the amounts of enterprises that are registered, among others. Through the analysis of the results it was observed that, in the commercial zone of Parnamirim-RN, the majority of entrepreneurs are male, most entrepreneurs are up to 30 years, and that about 76% of entrepreneurs make use of technologies to publicize its businesses and 82.93% of the projects correspond to the branch of commerce. The result of this research revealed in the southern zone of the commercial center of the municipality under study, was seen the great amount of the companies in the branch of the commerce, and few in the branch of services, and no company of the branch of industry. And this would be a factor for the economic development for the local population and contribution to the State, since the number of employment opportunities would grow, and with that, would develop an increase of the circulation of capital in the municipality.
Monografia
Keywords: Empreendedorismo; Empreendimentos; Empreendedores; Entrepreneurship; Enterprises; Entrepreneurs; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA